The miniaturist [videorecording (DVD)] - Taylor-Joy, Anya, 1996-; Garai, Romola, 1982-; Squires, Hayley; Burton, Jessie, 1982- (PBS, 2017)
A woman moves to live with her new husband in seventeenth century Amsterdam, but soon discovers that not everything is what it seems.